2020
DOI: 10.1016/j.jprot.2020.103920
|View full text |Cite
|
Sign up to set email alerts
|

Shell palaeoproteomics: First application of peptide mass fingerprinting for the rapid identification of mollusc shells in archaeology

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…It has previously been shown that exposure of shell biominerals to solutions of these chemicals for <3 hours causes no alteration to their composition or structure. 15,31,32 Even aer 240 hours (ten days) of oxidation with a less persistent oxidant, hydrogen peroxide, $50% of the original organic concentration persisted within the shell biomineral powders. 31 In the presence of biominerals with carbonate, hydrogen peroxide became less effective at oxidizing organic compounds; also hydrogen peroxide is thermodynamically unstable, decomposing into water and oxygen.…”
Section: Sample Preparationmentioning
confidence: 99%
“…It has previously been shown that exposure of shell biominerals to solutions of these chemicals for <3 hours causes no alteration to their composition or structure. 15,31,32 Even aer 240 hours (ten days) of oxidation with a less persistent oxidant, hydrogen peroxide, $50% of the original organic concentration persisted within the shell biomineral powders. 31 In the presence of biominerals with carbonate, hydrogen peroxide became less effective at oxidizing organic compounds; also hydrogen peroxide is thermodynamically unstable, decomposing into water and oxygen.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Of these matrix components, proteins are the best studied; their preservation in the mineral can lead to inferences of function and provide indirect genetic information in the absence of preserved DNA (e.g., Schroeter et al, 2017). Recent analyses have shown that intact endogenous peptides remain in invertebrate skeletons for 1000s-100,000s of years (Sakalauskaite et al, 2019;Drake L. et al, 2020b;Sakalauskaite et al, 2020). Across various taxa, intact peptides may retain amino acids longer in fossil specimens than if those biomolecules exist individually as free amino acids (Bada et al, 1999), allowing for detection of ecological and ocean chemistry signatures including the occurrence of photosymbiosis in fossil scleractinian corals (Muscatine et al, 2005;Tornabene et al, 2017) and past local nitrogen cycling regimes (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our study shows the good potential for preservation of some SMPs across archaeological times. It consequently paves the road of an emerging discipline, ‘palaeoshellomics’ ( Wallace and Schiffbauer, 2016 ; Sakalauskaite et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%